PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PENERAPAN PSAK 73 SEBAGAI VARIABEL MODERASI - Elisabeth; Estralita Trisnawati; Sriwati (Jurnal Kontemporer Akuntansi, 2025)
The purpose of this study is to examine the financial performance factors that affect firm value and to obtain evidence of the effect of the implementation of PSAK 73 on firm value in the years before and after the implementation of mandatory PSAK 73. This study uses 192 observation data from retail and transportation companies listed on the Indonesia Stock Exchange for 4 years from 2018 to 2021. The results of this study prove that (1) there are significant differences in the variables of profitability, solvency, capital intensity in the period before and after the implementation of PSAK 73. However, there is no significant difference in the value of company size and firm value before and after the implementation of PSAK 73. (2) financial performance in the form of profitability, solvency, has a significant positive effect on firm value. The moderating variable, PSAK 73 cannot moderate the relationship between financial performance and firm value. This shows that the implementation of PSAK 73 reported by various media as the cause of the decline in the performance of several companies listed on the stock exchange is not proven. This study also shows that the variables of profitability, solvency, company size, PSAK and capital intensity are able to explain the variable of company value by 62.72%.